Reentrant transitions of a mixed-spin Ising model on the diced lattice - Jascur, M.; Strecka, J. (Condensed Matter Physics, 2005)
Magnetic behaviour of a mixed spin-1/2 and spin-1 Ising model on the diced
lattice is studied using an exact star-triangle mapping transformation. It is
found that the uniaxial as well as biaxial single-ion anisotropy acting on the
spin-1 sites may potentially cause a reentrant transition with two consecutive
critical points. Contrary to this, the effect of next-nearest-neighbour interaction
between the spin-1/2 sites possibly leads to a reentrant transition
with three critical temperatures in addition to the one with two critical points
only. The shape of the total magnetization versus temperature dependence
is particularly investigated for the case of ferrimagnetically ordered system. Магнітна поведінка змішаної спін-1/2 та спін-1 моделі Ізинга на
гратці типу грального кубіка досліджується з використанням точного
перетворення співставлення зірка-трикутник. Отримано, що як уніаксіальна так і біаксіальна анізотропія іона, діючи на вузли зі
спіном-1, потенційно можуть спричинити перехід повернення з
двома послідовними критичними точками. На противагу цьому,
ефект взаємодії наступних за найближчими сусідами між вузлами
зі спінами-1/2 ймовірно приводить до спадного переходу з трьома
критичними температурами додатково до переходу з лише двома
критичними точками. Форма залежності повного намагнічення від
температури досліджується, зокрема, для випадку ферімагнітно
впорядкованих систем.